Building nationalism through history lessons for high school students in the city of Padangsidimpuan - Burhanuddin (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The portrait of Indonesia's national education today is experiencing a downturn. A number of problems still surround our world of education. The problem is not only in the form of equal distribution of educational opportunities, quality improvement and facilities, but also the low level of relevance of education to the needs of the world of work. This study aims to find out: 1) The values ??of nationalism contained in history lessons, 2) Learning strategies for building nationalism carried out by history teachers, 3) Obstacles experienced by history teachers in increasing a sense of nationalism, 4) Results achieved history teacher in increasing a sense of nationalism. The results obtained are that students can cultivate the values ??of nationalism such as discipline, honesty, diversity/diversity, unity and similarity. By using the lecture, discussion and question and answer methods as well as interesting media, relevant sources, motivation and reinforcement on the material on the Nationalism Movement in Indonesia, history teachers at Padangsidimpuan Senior High School can instill a sense of nationalism in students.